2021
DOI: 10.4062/biomolther.2020.192
|View full text |Cite
|
Sign up to set email alerts
|

Interruption of Helicobacter pylori-Induced NLRP3 Inflammasome Activation by Chalcone Derivatives

Abstract: Helicobacter pylori causes chronic gastritis through cag pathogenicity island (cagPAI), vacuolating cytotoxin A (VacA), lipopolysaccharides (LPS), and flagellin as pathogen-related molecular patterns (PAMPs), which, in combination with the pattern recognition receptors (PRRs) of host cells promotes the expression and secretion of inflammation-causing cytokines and activates innate immune responses such as inflammasomes. To identify useful compounds against H. pylori-associated gastric disorders, the effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 46 publications
2
14
0
Order By: Relevance
“…And these flavonoids also inhibited IκBζ activation. The inhibitory mechanisms were similar to those of flavonoids on the H. pylori -induced inflammasome pathway ( Choi et al ., 2021 ). The strongest inhibitors were apigenin and kaempferol.…”
Section: Low-dose Systemic Treatment With Flavonoidssupporting
confidence: 61%
See 1 more Smart Citation
“…And these flavonoids also inhibited IκBζ activation. The inhibitory mechanisms were similar to those of flavonoids on the H. pylori -induced inflammasome pathway ( Choi et al ., 2021 ). The strongest inhibitors were apigenin and kaempferol.…”
Section: Low-dose Systemic Treatment With Flavonoidssupporting
confidence: 61%
“…In a continuing study, THP-1 cells activated with H. pylori were treated with chalcone derivatives. In H. pylori -stimulated cells, chalcones such as 2’-hydroxy-4’,6’-dimethoxyflavone and 2’-hydroxy-3,4,5-trimethoxyflavone strongly inhibited NLRP3 inflammasome activation without affecting the expression levels of the inflammasome components, NLRP3, ASC, and procaspase-1 ( Choi et al ., 2021 ). The cellular action mechanisms of the chalcones include inhibiting the interferon-1 receptor-associated kinase 4 (IRAK4) and IκBα/NF-κB signaling pathways.…”
Section: Local Treatment With Flavonoidsmentioning
confidence: 99%
“… 35 , 39 Reduced leptin levels induce appetite, which leads to overfeeding, resulting in overweight and obesity. 40 …”
Section: Discussionmentioning
confidence: 99%
“…Children 2022, 9, 121 2 of 17 lymphomas [1,2]. It was previously demonstrated that H. pylori-associated inflammation is closely related to the host's innate immune system since it is capable of triggering these responses via particular pathogenicity features such as cag-pathogenicity island (cagPAI) and vacuolating cytotoxin A (VacA), or pathogen-associated molecular patterns (PAMPs), involving flagellin and lipopolysaccharides (LPS) [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…According to the World Health Organization, Helicobacter pylori ( H. pylori ) is a class 1 carcinogen, infecting more than 50% of the world’s population. It is well-documented that this infection might lead to chronic gastritis, peptic ulcers, gastric cancer, and mucosa-associated lymphoid tissue lymphomas [ 1 , 2 ]. It was previously demonstrated that H. pylori -associated inflammation is closely related to the host’s innate immune system since it is capable of triggering these responses via particular pathogenicity features such as cag-pathogenicity island (cagPAI) and vacuolating cytotoxin A (VacA), or pathogen-associated molecular patterns (PAMPs), involving flagellin and lipopolysaccharides (LPS) [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%